2010
DOI: 10.1111/j.1095-8649.2009.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine control by dopamine of teleost reproduction

Abstract: While gonadotropin-releasing hormone (GnRH) is considered as the major hypothalamic factor controlling pituitary gonadotrophins in mammals and most other vertebrates, its stimulatory actions may be opposed by the potent inhibitory actions of dopamine (DA) in teleosts. This dual neuroendocrine control of reproduction by GnRH and DA has been demonstrated in various, but not all, adult teleosts, where DA participates in an inhibitory role in the neuroendocrine regulation of the last steps of gametogenesis (final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 193 publications
(273 reference statements)
4
130
1
2
Order By: Relevance
“…In rats, catechol estrogens decrease the turnover rate of dopamine in the corpus striatum [48]. Also, animal studies have shown that dopamine influences GnRH production at the level of the hypothalamus [49][50][51][52]. In fact, in vitro data suggest that dopamine can stimulate GnRH secretion from the human hypothalamus [53].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, catechol estrogens decrease the turnover rate of dopamine in the corpus striatum [48]. Also, animal studies have shown that dopamine influences GnRH production at the level of the hypothalamus [49][50][51][52]. In fact, in vitro data suggest that dopamine can stimulate GnRH secretion from the human hypothalamus [53].…”
Section: Discussionmentioning
confidence: 99%
“…This begins with hypothalamic synthesis and synaptic release of peptide gonadotropin-releasing hormones (GnRH) onto the gonadotropic cells of the pituitary gland, where they stimulate the synthesis and release of the protein hormones, follicle-stimulating hormone (FSH) and luteinising hormone (LH) (reviewed in Planas and Swanson 2008;LevaviSivan et al 2010;Zohar et al 2010). In many species, there is also inhibitory tone imposed by the action of dopamine (DA)-secreting neurones, with the release of FSH and LH being dependent on the balance between GnRH stimulation and DA inhibition (reviewed in Dufour et al 2010). The GnRH-pituitary interaction is further modulated by melatonin produced by the light-sensitive pineal gland by as-yet poorly understood mechanisms (reviewed in Migaud et al 2010), by the kisspeptin system through direct effects on the activity of GnRH-producing neurones (reviewed in Akazome et al 2010) and by the feedback effects of gonadal steroids (reviewed in Pankhurst 2008).…”
Section: Reproductionmentioning
confidence: 99%
“…Teleosts exhibit CA neuronal populations and innervation patterns in nuclei with proposed homologies to those found in tetrapods where they are known to modulate motivated social and reproductive behavior (Goodson and Kingsbury, 2013;Petersen et al, 2013). However, aside from DA neurons in the anterior preoptic area that are well documented to regulate the hypothalamic-pituitary-gonadal (HPG) axis in teleosts (Dufour et al, 2010;Dufour et al, 2005;Kah et al, 1987;Peter and Fryer, 1983), the function of specific CA cell groups in teleosts are largely unknown. However, recent studies in teleosts have begun to characterize cFos induction of CA nuclei to social challenge stimuli (O'Connell et al, 2013;Petersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%